Optimal operation of combined cooling heat and power (CCHP) systems in future energy networks - Huang, Xiaowei (Nanyang Technological University, 2020)
With the rapid development of the energy industry, the distributional energy network, energy storage technology, and some new energy technologies have been rapidly developed and promoted in recent years. CCHP (Combined cooling, heat, and power) system is also known as combined generation system of heat, cooling, and power, distributed combined generation system is a solution for comprehensive cascade utilization of energy. It is a kind of integrated energy supply method which combines the power generation system with the CCHP systems on a small scale near the consumers. The CCHP system not only enables the owner to become an energy supply system, but also can operate with the large power grid, and the system has the relative independence, flexibility and security. The CCHP system can operate independently and in parallel and can meet the needs of consumers with different power loads. In this project, to optimize the operation of the CCHP system, different models are established. An optimal method based on Yalmip toolbox in Matlab is used to minimize the total cost and maximize the customers’ benefits. A comparison and conclusion will be made on basis of the optimal results. Moreover, the operations of appliances in the HVAC system are also scheduled in this project.